Towards a knowledge-based society - Deshpande, J.V. (2006)
Reservations in institutes of higher education may not ideally ensure the production of high quality research and knowledge, necessary for a country's development and for its very self-preservation. This article suggests that apart from ensuring the spread of universal primary education, efforts should be invested to set in place mechanisms to spot, nurture and direct talent at the primary school stage itself so that children's abilities, irrespective of caste or any other identity restrictions, are molded towards the search for excellence. - Reproduced.
Keywords: Knowledge society